Association of clinical response criteria and disease activity levels with axial spondyloarthritis core domains: results from two phase 3 randomised studies, BE MOBILE 1 and 2 - Sofia Ramiro; Atul Deodhar; Philip J Mease; Martin Rudwaleit; Jonathan Kay; Marina Magrey; Victoria Navarro-Compán; Vanessa Taieb; Carmen Fleurinck; Ute Massow; Michael F Mørup; Christine de la Loge (RMD Open, 2024)
Objective To assess how achievement of increasingly stringent clinical response criteria and disease activity states at week 52 translate into changes in core domains in patients with non-radiographic (nr-) and radiographic (r-) axial spondyloarthritis (axSpA).Methods Patients in BE MOBILE 1 and 2 achieving different levels of response or disease activity (Assessment of SpondyloArthritis International Society (ASAS) and Ankylosing Spondylitis Disease Activity Score (ASDAS) response criteria, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI50)) at week 52 were pooled, regardless of treatment arm. Associations between achievement of these endpoints and change from baseline (CfB) in patient-reported outcomes (PROs) measuring core axSpA domains, including pain, fatigue, physical function, overall functioning and health, and work and employment, were assessed.Results Achievement of increasingly stringent clinical efficacy endpoints at week 52 was generally associated with sequentially greater improvements from baseline in all PROs. Patients with nr-axSpA achieving ASAS40 demonstrated greater improvements (CfB) than patients who did not achieve ASAS40 but did achieve ASAS20, in total spinal pain (−5.3 vs −2.8, respectively), Functional Assessment of Chronic Illness-Fatigue subscale (12.7 vs 6.7), Bath Ankylosing Spondylitis Function Index (−3.9 vs −1.8), European Quality of Life 5-Dimension 3-Level Version (0.30 vs 0.16), Work Productivity and Activity Impairment-axSpA presenteeism (−35.4 vs −15.9), overall work impairment (−36.5 vs −12.9), activity impairment (−39.0 vs −21.0) and sleep (9.0 vs 3.9). Results were similar for ASDAS and BASDAI50. Similar amplitudes of improvement were observed between patients with nr-axSpA and r-axSpA.Conclusions Patients treated with bimekizumab across the full axSpA disease spectrum, who achieved increasingly stringent clinical response criteria and lower disease activity at week 52, reported larger improvements in core axSpA domains.